Floral Nectary Anatomy and Ultrastructure in Mycoheterotrophic Plant, Epipogium aphyllum Sw. (Orchidaceae) - Emilia Święczkowska; Agnieszka K. Kowalkowska (The Scientific World Journal)
Epipogium aphyllum is a European-Asian obligatory mycoheterotrophic orchid containing no chlorophyll. Flowers are not resupinate with a sack-shape spur and cordate lip, which is divided into two parts: the basal (hypochile) and distal one (epichile). The floral analysis provides strong evidence to conclude that nectar is secreted on the upper surface of pink-coloured papillate ridges and epidermal (adaxial) cells at different place in spur, especially at the apex. The exudation on papillae has been observed through the entire anthesis and it has been stained on polysaccharides, proteins, and lipids. The dense cytoplasm of papillae contains profuse endoplasmic reticulum, plentiful vesicles (bigger ones with tannin-like materials), numerous mitochondria, sometimes dictyosomes, starch grains, and plastids with tubular structures. The large electron-dense bodies in cell walls are structurally the same as tannin-like materials from vesicles that are in contact with plasmalemma. The rupture of thin layer of swelled cuticle is caused by pressure of gathered substances exuded due to granulocrine secretion. The idioblasts with raphides occur mainly in tepals tissue. The dynamic changes of the nectar exudation, released through endocrine secretion, have been noticeable during the anthesis: both on the lip and inside the spur. The nectar secretion is not dependent on the colour form of E. aphyllum blooming shoots. The floral biology and ultrastructure differ from mycoheterotrophic plants known up to date.